Creative Digital Marketing and Advanced Internetworking Assistance Programs for Micro, Small and Medium Enterprises in Buah Batu District Bandung - Bethani Suryawardani; Astri Wulandari; Dandy Marcelino; Gandeva Bayu Satrya; Rahmadi Wijaya; Wahyu Lukito; Bijaksana Prabawa (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Digital media can support Micro, Small, and Medium Enterprise (MSME) businesses to increase brand awareness of their products, so they can gain competitive advantages and reach a broader market. Unfortunately, not all MSME businesses have the capabilities to utilize digital media to support their businesses. The MSMEs in Buah Batu district face problems that can not be resolved by conventional marketing methods, such as lack of brand awareness and drop in sales which results in the decrease of their revenues and profits. This Community Service aims to improve the MSME's knowledge and skills on creative digital marketing strategy and their understanding of the marketplace so they can create online stores for their businesses. Online stores make it feasible for those MSMEs to broaden their market reach. For the problems related to the IT area, the team will provide network training. The method applied was the service-learning approach. The results of this community service are that the MSMEs in Buah Batu District are capable to create their online shops, promote their products through the marketplace and social media and finally increase their revenues. The output of these community service activities is the design of MSME product packaging and website.